تصور مقترح لتطوير منهج الاقتصاد المنزلي لتعزيز الأمن الفكري لدى طالبات المرحلة الإعدادية في ضوء أبعاد جودة الحياة - عمر، زيزي حسن (الجمعية المصرية للاقتصاد المنزلي, 2019)
هدف البحث إلى وضع تصور مقترح لتطوير منهج الاقتصاد المنزلي لتعزيز الأمن الفكري لدى طالبات المرحلة الإعدادية في ضوء أبعاد جودة الحياة، وتم استخدام المنهج الوصفي التحليلي من خلال تحليل المنهج وتطبيق أدوات البحث والتي أظهرت النتائج التالية: وجود قصور في مناهج الاقتصاد المنزلي للمرحلة الإعدادية في تضمينها لمراحل الأمن الفكري، وأبعاد جودة الحياة، ومن خلال تحليل محتوى منهج الاقتصاد المنزلي للمرحلة الإعدادية تم التوصل لرؤية مستقبلية لتطوير المنهج ليستند إلى اتساق جميع مكونات المنهج لسهولة تضمين جميع مراحل الأمن الفكري وأبعاد جودة الحياة، وقد خرج البحث بمجموعة من التوصيات أهمها توجيه نظر متخصصي مناهج وبرامج الاقتصاد المنزلي في جميع المراحل التعليمية على تضمين مراحل الأمن الفكري في المناهج كخطوة لتحقيق أبعاد جودة الحياة.
The study aimed at deducting Suggested Perspective to develop a Home Economics curriculum for Promoting Intellectual Security for preparatory female pupils In the light of life of Quality, The research used the descriptive and analytical approach by analyzing the curriculum and study tools, the results showed that: there are shortage afflicts of home economics curriculum for preparatory stage in the inclusion of the ways of Intellectual Security and life of Quality, Through analyzing the content of home economics curriculum for preparatory stage, it was reached to a future vision had formed in general instructions form development that based on a consistent vision for all the components of curriculum, so for embodiment to all the ways of Intellectual Security and life of Quality, The research recommended that: there are a Necessary need to Directing the attention of specialized in curricula and programs for home economics in all educational stages embodiment Intellectual Security in curriculum to develop life of Quality.
Keywords: تطوير المناهج -- منهج الاقتصاد المنزلي -- الأمن الفكري -- جودة الحياة -- المرحلة الإعدادية